Moderate Conventionalism and Cultural Appropriation - Räikkä Juha; Puumala Mikko (NTNU Programme for Applied Ethics/ Norwegian University of Science and Technology Library, 2022)
Abstract
Cultural appropriation, also called cultural borrowing, has been the topic of much discussion in recent years. Roughly speaking, cultural appropriation happens when someone outside of a cultural or ethnic group takes or uses some object that is characteristic or in some way important to the group without the group’s permission. Individuals who find cultural appropriation (or borrowing) unproblematic have often argued that if we express moral criticism of the use of traditional Sami outfits by non-Sami, then we are logically committed to criticize all kinds of habits that are clearly acceptable –such as using jeans, eating pizza or drinking tea. However, we will argue that in many cases that objection is problematic. We point out that if one social habit or practice is prohibited (or supported) by existing social conventions but another is not, then there is a convention difference between the cases. The convention difference is in turn a morally relevant difference, or so we aim to show. We refer to “moderate conventionalism,” according to which existing social conventions are morally relevant facts that should be taken into account when choosing how to act, whatever the content of the conventions happens to be. The claim is analogous with the traditional view that laws have some moral relevance and binding force independent of their content.